Atomistic insights into the structure and elasticity of densified 45S5 bioactive glasses - Ouldhnini, Youssef; Atila, Achraf; Ouaskit, Said; Hasnaoui, Abdellatif (Physical Chemistry Chemical Physics, 2021)
Glasses have applications in regenerative medicine due to their bioactivity, enabling interactions with hard and soft tissues. Soda-lime phosphosilicate glasses, such as 45S5, represent a model system of bioactive glasses. Regardless of their importance as bioactive materials, the relationship between the structure, density, and cooling process has not been studied in detail. This hinders further development of glasses as biomaterials. We used molecular dynamics simulations to study the elastic and structural properties of densified 45S5 bioactive glass and liquids over a wide range of densities. We performed a systematic analysis of the glass structure to density relationship to correlate the change in the properties with the structural change to enhance the mechanical properties of bioactive glasses while preserving their bioactive nature. The results show that the glass structure tends to be repolymerized, as indicated by increased network connectivity and a tetrahedral to octahedral polyhedral transition. We were able to tailor the elastic properties while keeping the bioactivity of the glass. The results presented here will provide some guidance to develop bioactive glasses with enhanced mechanical properties.
CRIS-Team WoS Importer:2021-07-23